RGB color analysis of formaldehyde in vegetables based on DNA functionalized gold nanoparticles and triplex DNA. Issue 36 (1st September 2022) - Huang, Wenxiu; Zhao, Lizhen; Shen, Ruidi; Li, Gongke; Ling, Liansheng
Abstract : We developed an RGB color analysis for the detection of formaldehyde (FA) by using a DNA functionalized gold nanoparticle probe. Abstract : A highly sensitive and selective RGB color analysis for the detection of formaldehyde (FA) was developed by using a DNA functionalized gold nanoparticle (AuNPs-DNA) probe. When complementary oligonucleotides (oligo 2 and oligo 3) and a silver ion (Ag + ) were added to the AuNPs-DNA solution, triplex DNA was formed, resulting in the aggregation of AuNPs, and accompanied by a solution color change from red to purple. With the addition of formaldehyde, it reacted with Ag +, decreased the stability of triplex DNA between AuNPs–DNA, induced the dispersion of AuNPs, and the color of AuNPs recovered to red. Therefore, the formaldehyde concentration could be estimated with the RGB (red, green, blue) values of the AuNP solution by using a smartphone application (APP). The R value of the system was proportional to the concentration of formaldehyde within the range of 0.23–4.50 mg L −1, with a detection limit of 0.14 mg L −1 . The method has been successfully applied to detect the residues of formaldehyde in vegetable samples and has the potential of the on-site determination of formaldehyde.